Perancangan Alat Penyemprotan Tanaman Cabai Sistem Kontrol Otomatis Berbasis IoT - Rizkitinus, Fina; Eko Purnomo, Fendik; Adzar Prayoga, Fahrizal; ifnil mubarok, Diki; Ristaulia, Nasikhatul; Reza Rabani, Muhammad (AI Society & STMIK Indonesia, 2025)
The application of Internet of Things (IoT) technology in the agricultural sector provides innovative solutions in managing chili plant pests. This study aims to design an IoT-based pesticide sprayer with automatic control using Arduino, ESP32, and solar panel energy sources. The Research and Development (R&D) method is used, including problem identification, planning, product development, trials, evaluations, and field validation. The test results show that this tool is capable of spraying water or pesticides up to a distance of 5 meters with a spraying area of 10 m² per cycle. With a spray capacity of up to 12 liters per cycle, this tool has succeeded in reducing the whitefly pest population by 70% and increasing chili plant productivity by 30% compared to manual methods. Energy usage analysis shows the efficiency of the tool through the use of 120 Wp solar panels and 12V 100Ah batteries that support pump operations for 1 hour 48 minutes. This study provides a sustainable solution for managing plant pests and increasing crop yields effectively by utilizing renewable energy.